Beautiful Double Sum

Calculus Level 5

k = 1 j = 1 [ H j ( H k + 1 1 ) k j ( k + 1 ) ( j + k ) ] = A B π C D ζ ( E ) + F G π H ζ ( I ) + J ζ ( K ) \sum _{ k=1 }^{ \infty }{ \sum _{ j=1 }^{ \infty }{ \left[ \frac { { H }_{ j }\left( { H }_{ k+1 }-1 \right) }{ kj\left( k+1 \right) \left( j+k \right) } \right] } } =\frac { -A }{ B } { \pi }^{ C }-D\zeta \left( E \right) +\frac { F }{ G } { \pi }^{ H }\zeta \left( I \right) +J\zeta \left( K \right)

The above equation is true for positive integers A , B , , K A,B, \ldots ,K , where A , B A,B and F , G F,G are pairwise coprime.

Find A + B + + K A+B+ \cdots +K .

Notation : ζ ( ) \zeta(\cdot) denotes the Riemann zeta function .


The answer is 29.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Consider the sum : S = n = 1 H n ( 1 n 1 n + k ) \displaystyle S=\sum_{n=1}^{\infty} {\rm H}_n (\frac{1}{n}-\frac{1}{n+k})

Note that , S = m = 1 n 1 m n = 1 ( 1 n 1 n + k ) = m 1 1 m n = m H n ( 1 n 1 n + k ) \displaystyle S=\sum_{m=1}^{n}\frac{1}{m} \sum_{n=1}^{\infty}(\frac{1}{n}-\frac{1}{n+k}) = \sum_{m\ge 1}\frac{1}{m}\sum_{n=m}^{\infty} {\rm H}_n (\frac{1}{n}-\frac{1}{n+k})

By telescoping & partial fraction decomposition we have , S = ζ ( 2 ) + n = 1 k 1 H n n = ζ ( 2 ) + 1 2 ( H k 1 ( 2 ) + ( H k 1 ) 2 ) \displaystyle S= \zeta(2) + \sum_{n=1}^{k-1} \frac{{\rm H}_n}{n} = \zeta(2) + \frac{1}{2}({\rm H}_{k-1}^{(2)} + ({\rm H}_{k-1})^2)

The main sum I = k = 1 j = 1 [ H j ( H k + 1 1 ) k j ( k + 1 ) ( j + k ) ] = k 1 H k + 1 1 k 2 ( k + 1 ) j 1 H j j ( j + k ) \displaystyle I = \sum _{ k=1 }^{ \infty }{ \sum _{ j=1 }^{ \infty }{ \left[ \frac { { H }_{ j }\left( { H }_{ k+1 }-1 \right) }{ kj\left( k+1 \right) \left( j+k \right) } \right] } } = \sum_{k\ge 1} \frac{{\rm H}_{k+1}-1}{k^2(k+1)} \sum_{j\ge 1} \frac{{\rm H}_j}{j(j+k)}

Using the above result and expanding the main sum after substituting values for the inner sum we have ,

I = 1 2 n 1 H n ( H n ) 2 n 2 + 1 2 n 1 H n 3 n 2 n 1 H n 2 n 3 + π 2 6 6 n 1 H n n 2 ζ ( 2 ) \displaystyle I = \frac{1}{2} \sum_{n\ge 1}\frac{{\rm H}_n ({\rm H}_{n})^2}{n^2} + \frac{1}{2}\sum_{n\ge 1} \frac{{\rm H}_{n}^{3}}{n^2}-\sum_{n\ge 1} \frac{{\rm H}_{n}^{2}}{n^3}+\frac{\pi^2 -6 }{6}\sum_{n\ge 1}\frac{{\rm H}_{n}}{n^2} - \zeta(2)

Categorising our four sums i.e. ,

n 1 H n ( H n ) ( 2 ) n 2 (*) \displaystyle \sum_{n\ge 1}\frac{{\rm H}_n ({\rm H}_{n})^{(2)}}{n^2} \text{ (*)}

n 1 H n 3 n 2 (**) \displaystyle \sum_{n\ge 1} \frac{{\rm H}_{n}^{3}}{n^2} \text{ (**)}

n 1 H n 2 n 3 (***) \displaystyle \sum_{n\ge 1} \frac{{\rm H}_{n}^{2}}{n^3} \text{ (***)}

n 1 H n n 2 (****) \displaystyle \sum_{n\ge 1}\frac{{\rm H}_{n}}{n^2} \text{ (****)}

Before we get into the sums define the multiple zeta functions as , ζ ( a , b , c ) = m = 1 n = 1 m 1 p = 1 n 1 1 m a n b p c \displaystyle \zeta(a,b,c) = \sum_{m=1}^{\infty} \sum_{n=1}^{m-1}\sum_{p=1}^{n-1} \frac{1}{m^a n^b p^c} & ζ ( a , b ) = m = 1 n = 1 m 1 1 m a n b \displaystyle \zeta(a,b) = \sum_{m=1}^{\infty} \sum_{n=1}^{m-1} \frac{1}{m^a n^b}

**** \text{****} Easily follows from euler sums and is n 1 H n n 2 = 2 ζ ( 3 ) \displaystyle \sum_{n\ge 1} \frac{{\rm H}_n}{n^2} = 2\zeta(3)

For *** \text{***} , Let J = n 1 H n 2 n 3 \displaystyle J = \sum_{n\ge 1} \frac{{\rm H}_{n}^{2}}{n^3}

A relationship between MZV & MHS values states that n = 1 H n ( a 1 , a 2 , a 3 , , a k ) n a = ζ ( a 1 , a 2 , , a k ) + ζ ( a + a 1 , a 2 , a 3 , , a k ) \displaystyle \sum_{n=1}^{\infty} \frac{{\rm H}_n(a_1,a_2,a_3,\cdots,a_k)}{n^a} = \zeta(a_1,a_2,\cdots,a_k)+\zeta(a+a_1,a_2,a_3,\cdots,a_k)

The quasi-shuffle identity shows that , H n 2 ( 1 ) = 2 H n ( 1 , 1 ) + H n ( 2 ) \displaystyle {\rm H}_n^2(1) = 2{\rm H}_n(1,1)+{\rm H}_n(2) & using the relationship above we make the sum equal to,

J = 2 ζ ( 3 , 1 , 1 ) + 2 ζ ( 4 , 1 ) + ζ ( 3 , 2 ) + ζ ( 5 ) \displaystyle J=2\zeta(3,1,1)+2\zeta(4,1)+\zeta(3,2)+\zeta(5)

Calculating the multiple zeta values we get , n 1 H n 2 n 3 = 7 2 ζ ( 5 ) ζ ( 2 ) ζ ( 3 ) \displaystyle \sum_{n\ge 1} \frac{{\rm H}_{n}^{2}}{n^3} = \frac{7}{2}\zeta(5)-\zeta(2)\zeta(3)

Next for ** \text{**} , It can be shown similarly that n 1 H n 3 n 2 = 10 ζ ( 5 ) + ζ ( 2 ) ζ ( 3 ) \displaystyle \sum_{n\ge 1} \frac{{\rm H}_{n}^{3}}{n^2} = 10\zeta(5)+\zeta(2)\zeta(3)

Coming to the most complicated sum that is * \text{*} ,

We begin with writing G = n 1 H n ( H n ) ( 2 ) n 2 = n 1 H n 1 ( H n 1 ) ( 2 ) n 2 + n 1 H k 1 ( 2 ) k 3 + H k 1 k 4 + ζ ( 5 ) \displaystyle G=\sum_{n\ge 1}\frac{{\rm H}_n ({\rm H}_{n})^{(2)}}{n^2} = \sum_{n\ge 1}\frac{{\rm H}_{n-1} ({\rm H}_{n-1})^{(2)}}{n^2} + \sum_{n\ge 1} \frac{{\rm H}_{k-1}^{(2)}}{k^3}+\frac{{\rm H}_{k-1}}{k^4}+\zeta(5)

Using MZV , G = n 1 H n 1 ( H n 1 ) ( 2 ) n 2 + ζ ( 3 , 2 ) + ζ ( 4 , 1 ) + ζ ( 5 ) \displaystyle G = \sum_{n\ge 1}\frac{{\rm H}_{n-1} ({\rm H}_{n-1})^{(2)}}{n^2} + \zeta(3,2)+\zeta(4,1)+\zeta(5)

Now using quasi-shuffle identity and multiple zeta ,

n 1 H n 1 ( H n 1 ) ( 2 ) n 2 = ζ ( 2 , 2 , 1 ) + ζ ( 2 , 1 , 2 ) + ζ ( 2 , 3 ) = 2 ζ ( 2 , 3 ) + ζ ( 3 , 2 ) \displaystyle \sum_{n\ge 1}\frac{{\rm H}_{n-1} ({\rm H}_{n-1})^{(2)}}{n^2} = \zeta(2,2,1)+\zeta(2,1,2)+\zeta(2,3)=2\zeta(2,3)+\zeta(3,2)

Thus n 1 H n ( H n ) ( 2 ) n 2 = ζ ( 5 ) + ζ ( 2 ) ζ ( 3 ) \displaystyle \sum_{n\ge 1}\frac{{\rm H}_n ({\rm H}_{n})^{(2)}}{n^2} = \zeta(5)+\zeta(2)\zeta(3)

Finally we derive , k = 1 j = 1 [ H j ( H k + 1 1 ) k j ( k + 1 ) ( j + k ) ] = ζ ( 2 ) 2 ζ ( 3 ) + 4 ζ ( 2 ) ζ ( 3 ) + 2 ζ ( 5 ) \displaystyle \sum _{ k=1 }^{ \infty }{ \sum _{ j=1 }^{ \infty }{ \left[ \frac { { H }_{ j }\left( { H }_{ k+1 }-1 \right) }{ kj\left( k+1 \right) \left( j+k \right) } \right] } } = -\zeta(2)-2\zeta(3)+4\zeta(2)\zeta(3)+2\zeta(5) which makes the answer 29 \boxed{29}

Note For MZV relations used above : \text{Note For MZV relations used above : } ,

ζ ( 4 , 1 ) = ζ ( 5 ) ζ ( 3 , 2 ) ζ ( 2 , 3 ) (1) \zeta(4,1) = \zeta(5)-\zeta(3,2)-\zeta(2,3) \text{ (1)}

ζ ( 4 , 1 ) = x = 1 y = 1 x 1 1 x 4 y = x = 1 y = 1 x 1 1 x 4 ( x y ) , reindexing the second sum = x = 1 y = 1 x 1 ( 1 x 4 y 1 x 3 y 2 1 x 2 y 3 1 x y 4 + 1 ( x y ) y 4 ) , = ζ ( 4 , 1 ) ζ ( 3 , 2 ) ζ ( 2 , 3 ) + x = 1 y = 1 x 1 ( 1 ( x y ) y 4 1 x y 4 ) = ζ ( 4 , 1 ) ζ ( 3 , 2 ) ζ ( 2 , 3 ) + x = 1 y = 1 x 1 1 y 4 ( 1 x y 1 x ) = ζ ( 4 , 1 ) ζ ( 3 , 2 ) ζ ( 2 , 3 ) + y = 1 1 y 4 x = y + 1 ( 1 x y 1 x ) , = ζ ( 4 , 1 ) ζ ( 3 , 2 ) ζ ( 2 , 3 ) + y = 1 1 y 4 x = 1 y 1 x , as the sum telescopes = ζ ( 4 , 1 ) ζ ( 3 , 2 ) ζ ( 2 , 3 ) + ζ ( 4 , 1 ) + ζ ( 5 ) = ζ ( 5 ) ζ ( 3 , 2 ) ζ ( 2 , 3 ) . \begin{aligned} \zeta(4,1) &= \sum_{x=1}^{\infty} \sum_{y=1}^{x-1} \frac{1}{x^4 y} \\ &= \sum_{x=1}^{\infty} \sum_{y=1}^{x-1} \frac{1}{x^4 (x-y)}, \text{ reindexing the second sum} \\ &= \sum_{x=1}^{\infty} \sum_{y=1}^{x-1} \left(-\frac{1}{x^4 y} - \frac{1}{x^3 y^2} - \frac{1}{x^2y^3} - \frac{1}{x y^4} + \frac{1}{(x-y)y^4}\right), \\ &\:\:\:\:\: \\ &= - \zeta(4,1) - \zeta(3,2) - \zeta(2,3) + \sum_{x=1}^{\infty} \sum_{y=1}^{x-1} \left(\frac{1}{(x-y)y^4} - \frac{1}{x y^4} \right) \\ &= - \zeta(4,1) - \zeta(3,2) - \zeta(2,3) + \sum_{x=1}^{\infty} \sum_{y=1}^{x-1} \frac{1}{y^4} \left(\frac{1}{x-y} - \frac{1}{x} \right) \\ &= - \zeta(4,1) - \zeta(3,2) - \zeta(2,3) + \sum_{y=1}^{\infty} \frac{1}{y^4} \sum_{x=y+1}^{\infty} \left(\frac{1}{x-y} - \frac{1}{x} \right), \\ & \:\:\:\:\: \\ &= - \zeta(4,1) - \zeta(3,2) - \zeta(2,3) + \sum_{y=1}^{\infty} \frac{1}{y^4} \sum_{x=1}^y \frac{1}{x}, \text{ as the sum telescopes} \\ &= - \zeta(4,1) - \zeta(3,2) - \zeta(2,3) + \zeta(4,1) + \zeta(5) \\ &= \zeta(5) - \zeta(3,2) - \zeta(2,3). \square \end{aligned}

ζ ( 2 , 2 , 1 ) + ζ ( 2 , 1 , 2 ) = ζ ( 2 , 3 ) + ζ ( 3 , 2 ) (2) \zeta(2,2,1)+\zeta(2,1,2)=\zeta(2,3)+\zeta(3,2) \text{ (2)}

This is easy to see and rather a standard result so I'm skipping it.

Bravo! Nice one! Even I had the same solution.

Aditya Kumar - 4 years, 10 months ago

Yeah Thankss !!

Aditya Narayan Sharma - 4 years, 10 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...